Environmental Impacts of a Solar Dish Coupled With a Micro-Gas Turbine for Power Generation - Agostini, A.; Carbone, C.; Lanchi, M.; Miliozzi, A.; Misceo, M.; Russo, V. (Frontiers in Energy Research, 2021)
Concentrated Solar Power (CSP) systems are regarded as a renewable energy source technology which can contribute to decoupling the energy mix from fossil fuel combustion and related environmental impacts. However, current small scale CSP technologies (e.g. Dish-Stirling) have not entered the market yet, due to high costs, complexity and poor reliability. The EU funded OMSoP (Optimised Microturbine Solar Power) project aimed at solving the small scale CSP shortcomings by coupling a Solar Dish with the consolidated and relatively cheap technology of the Micro Gas Turbine (MGT). in this study an environmental life cycle assessment analysis of the production and operation of a CSP-MGT system, is performed following an eco-design approach, thus identifying the environmental hot-spots and how the system can be improved in terms of environmental impacts. The results of the analysis, per unit of electricity produced, were compared to other renewable technologies with the same level of dispatchability to better evaluate strengths and weaknesses of the system under exam. As regards climate change, the greenhouse gases emissions of the CSP-MGT system resulted in the same range of those generated by photovoltaic systems. However, the system can substantially be optimised and the greenhouse gases emissions per kWh can be reduced up to 73% with respect to the built prototype. The greenhouse gases emissions are much lower than the current Italian energy mix (by up to 94%). To reduce the environmental burden of CSP-MGT plants, the system design here considered should be revised by improving the components performance, and significantly reducing the reflective surface and therefore the structural materials for the dish foundation and frame. The replacement of steel in the dish frame with aluminium increases all the environmental impacts parameters and primary energy demand (17-27% depending on the environmental category considered), but slightly reduces abiotic elements depletion (by 9%).